Aspartic Acid Residue 51 of SaeR Is Essential for Staphylococcus aureus Virulence - Nygaard, Tyler K.; Borgogna, Timothy R.; Sward, Eli W.; Guerra, Fermin E.; Dankoff, Jennifer G.; Collins, Madison M.; Pallister, Kyler B.; Chen, Liang; Kreiswirth, Barry N.; Voyich, Jovanka M. (Frontiers in Microbiology, 2018)
Staphylococcus aureus is a common Gram-positive bacteria that is a major cause of human morbidity and mortality. The SaeR/S two-component sensory system of S. aureus is important for virulence gene transcription and pathogenesis. However, the influence of SaeR phosphorylation on virulence gene transcription is not clear. To determine the importance of potential SaeR phosphorylation sites for S. aureus virulence, we generated genomic alanine substitutions at conserved aspartic acid residues in the receiver domain of the SaeR response regulator in clinically significant S. aureus pulsed-field gel electrophoresis (PFGE) type USA300. Transcriptional analysis demonstrated a dramatic reduction in the transcript abundance of various toxins, adhesins, and immunomodulatory proteins for SaeR with an aspartic acid to alanine substitution at residue 51. These findings corresponded to a significant decrease in cytotoxicity against human erythrocytes and polymorphonuclear leukocytes, the ability to block human myeloperoxidase activity, and pathogenesis during murine soft-tissue infection. Analysis of SaeR sequences from over 8,000 draft S. aureus genomes revealed that aspartic acid residue 51 is 100% conserved. Collectively, these results demonstrate that aspartic acid residue 51 of SaeR is essential for S. aureus virulence and underscore a conserved target for novel antimicrobial strategies that treat infection caused by this pathogen.